IDENTIFICATION OF FATTY ACIDS IN ESSENTIAL VEGETABLE OILS MANUFACTURED IN KENYA USING GC- FID - Linda Wangeci Maina, Prof. D. K. Kariuki, Prof. O. M. Yusuf (EPRA International Journal of Research and Development (IJRD), 2022)
The aim of this research was to identification fatty acids using Gas Chromatography with a Flame Ionization Detector of edible vegetable oils manufactured in Kenya. Vegetable edible oils processed and refined in Kenya have not been characterized and hence it’s impossible to distinguish between them. Sunflower, Corn and Soya bean vegetable oils by using physiochemical parameters dependently without an identification methods. Twenty two samples comprising of nine Sunflower of three different brand type, nine Corn oils of three different brand type and four Soya bean oils of two different brand type were collected from various supermarkets in Nairobi. The samples were transported, prepared and stored in the refrigerator at 4°C. GC-FID (Hewlett-Packard 6890 gas chromatograph -Agilent Technologies) was used for separation and quantification of FAMES. The GC-FID analysis was done under specific parameters and within the validation procedure linearity, precision and recovery, limit of detection (LOD) and limit of quantification (LOQ) were investigated.